Eletrodeposição dos revestimentos FexCo100-x e FexNi100-x em solvente eutético cloreto de colina e ureia: caracterização e aplicação na reação de desprendimento de hidrogênio - Oliveira, Francisco Gilvane Sampaio de (2021)
The use of non-renewable energy sources, especially those of fossil origin, which make up about 81 % of the world’s energy matrix, has caused several environmental problems that are increasingly noticeable throughout society. In this scenario, the search for new alternative energy sources, which are clean and renewable, has gained more and more notoriety with the emphasis on green hydrogen, which is considered the most promising source of renewable energy. Therefore, the main objective of this investigation was the electrodeposition of FexCo100−x and FexNi100−x coatings obtained from eutectic mixture choline chloride-urea and applied as Hydrogen evolution reaction electrocatalysts in alkaline solutions. Furthermore, the materials’ morphological, structural, and magnetic properties were investigated to provide a detailed understanding of the influence of such parameters. Morphological analyzes revealed the formation of cracked surfaces in all FexCo100−x coatings, with the increase in Co concentration causing the cracks to become smaller. Moreover, such morphologies were also observed in the FexNi100−x coatings, however, as Ni contractions, greater than 31 % are added, the coatings morphology changes to agglomerates of spherical particles, which is a typical morphology of Ni-rich electrodeposits. The investigation by spectroscopy, Mössbauer confirmed the formation of the Fe-Co alloy in the following samples Fe87Co13, Fe64Co36, and Fe44Co56, as well as the Fe-Ni alloy was obtained only in the samples Fe89Ni11, Fe47Ni53, and Fe28Ni72. Besides, the fabrication of the Fe57Co43 alloy nanowires via electrodeposition was successfully carried out in the eutectic mixture choline chloride-urea, obtaining the desired morphology and crystalline structure. All materials produced in this investigation were tested as Hydrogen evolution reaction electrocatalysts, the electrocatalytic results showed that the materials have good performance, with results compatible with other catalytic materials based on transition metals reported in the literature. In particular, the binary coatings FexCo100−x and FexNi100−x, which although present electrocatalytic activity lower than pure Fe, the incorporation of Co or Ni metals provided the materials with more excellent stability and durability as shown in continuous operation tests. Finally, we can conclude that the eutectic mixture choline chloride-urea is an ideal alternative for electrodepositing Fe, Co, and Ni-based materials, since in this solvent the electrodeposition of such metals takes place efficiently without the need for complexing agents, moreover the solvent is biodegradable thus making the process environmentally friendly.